PREDICTION OF THE INSURANCE INDUSTRY DEMAND FOR A SPECIFIC MULTINATIONAL COMPANY - Koklar, Robin (European Scientific Journal, ESJ, 2014)
The work deals with the prediction of the insurance industry demand for a multinational company in the field of life and non-life insurance. A system of simultaneous equations was applied for estimation of industry demand in different countries. The advantage of using a set of simultaneous equations is that it is possible to estimate the development of the multiple markets simultaneously. The system of simultaneous equations is estimated by three-stage least squares model and prediction for the years 2012 and 2013 was solved with a dynamic stochastic model.